Combined influence of fin, phase change material, wick, and external condenser on the thermal performance of a double slope solar still. (10th March 2021) - Tuly, S.S.; Rahman, M.S.; Sarker, M.R.I.; Beg, R.A.
Abstract: This study focuses on the enhancement of potable water productivity of an active double slope modified solar still (SS) considering the combined effect of solid rectangular fin, paraffin wax as a thermal energy storage medium, black cotton cloth as wick material, and an external condenser. The performance of three double slope SSs (modified, finned, and traditional) is evaluated considering five different cases. A comparative assessment of the performances of three double slope SSs is performed and it is perceived that the supreme productivities are 3.07, 2.70, and 2.46 L/m 2 for modified, finned, and traditional SSs, respectively. The maximum efficiency of the modified SS with and without external condenser are found as 39.74% and 30%, respectively. An external condenser insertion in the modified SS boosts the productivity by approximately 10%. The average daily efficiency of the modified SS is 14.23% and 22.33% higher than the finned and traditional SS, respectively. The economic analysis is also conducted, and the cost per liter (CPL) values for traditional SS, the finned one, and the modified one are found as 0.0135, 0.0133, and 0.0117 $/L/m 2, respectively. The novel modification of SS could be a propitious alternative to meet up the potable water demand in remote regions with low cost.